The anti-inflammatory effect of leptin on experimental colitis: involvement of endogenous glucocorticoids - YEGEN, BERRAK; ERCAN, FERİHA (ELSEVIER SCIENCE INC, 2004)
The present study was designed to compare the effect of leptin on acute colonic inflammation with that of acute stress exposure, which acts via the hypothalamic-pituitary-adrenal (HPA) axis. Sprague-Dawley rats of both sexes were administered intrarectally with acetic acid. Either leptin (10 mug/kg; i.p.) or saline was injected immediately before and 6 h after the induction of colitis. A group of rats was exposed to water avoidance stress (WAS) for 30 min at the 6th h of colitis induction. RU-486 (2 mg/kg; i.p.), a glucocorticoid receptor antagonist, was injected intraperitoneally, at 12 and 1 h before the initial leptin injection, and at 1 h before the second leptin injection or exposure to WAS. Rats were decapitated at 24 h and the distal 8 cm of,the colon were removed for macroscopic and microscopic scoring, determination of tissue wet weight index (WI) and tissue myeloperoxidase activity (MPO). Acetic acid-induced colitis significantly increased macroscopic and microscopic damage scores, WI and MPO, compared to control group. Exposure to acute WAS or treatment with leptin reduced the elevations in damage scores, WI and MPO induced by colitis, but no additive inhibitory effect was observed when WAS and leptin were applied together. RU-486 treatment reversed the inhibitory effects of leptin or WAS on colonic inflammation. Our results demonstrate that exogenous leptin mimics the effects of HPA axis activation on colitis-induced inflammatory process. The results also suggest that the anti-inflammatory effect of leptin involves a tissue neutrophil-dependent mechanism and is dependent on the release of glucocorticoids. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: hypothalamo-pituitary-adrenal axis; water avoidance stress; ACTH; acetic acid colitis; myeloperoxidase activity; GASTROINTESTINAL-TRACT; EXPRESSION; STRESS; RATS; CHOLECYSTOKININ; INFLAMMATION; MECHANISMS; GENE; GASTROPROTECTION; SUSCEPTIBILITY